Analysis of Odd Mid-Semester Exam Questions (UTS) for Sports Learning at SMPIT Khairunnas, Bengkulu City - Ogik Jaya Saputra; Citra Dewi; Feby Elra Perdima (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the quality of the mid-semester exam questions for class X PJOK subjects at SMA N 1 Kembang with item analysis in terms of difficulty level, discriminating power and distractor level. This research is a quantitative descriptive research. This research was conducted by collecting some data including exam questions, answer keys, and student answer sheets which were then processed with the Anates Program Version 4.09. The subjects in this study were students of class X SMA N 1 Kembang with a total of 167 consisting of 5 classes. The overall results of the analysis of 50 multiple choice items. Judging from the level of difficulty, there are 14 questions (28%) in the difficult category, 22 questions (44%) in the medium category, 14 questions (28%) in the easy category. In terms of discriminating power, there are 13 questions (26%) in the bad category, 23 questions (46%) in the moderate category, 8 questions (16%) in the good category, and 6 questions (12%) in the very bad category. Judging from the effectiveness of the distractors, there are 7 questions (14%) in the very good category, 18 questions (36%) in the good category, 19 questions (38%) in the fairly good category, and 6 questions (12%) in the poor category.